2018
DOI: 10.4314/jfas.v9i4s.45
|View full text |Cite
|
Sign up to set email alerts
|

Assement on level of indoor air quality at kindergartens in Ampang Jaya, Selangor, Malaysia

Abstract: This study identify the air pollutant that occurs in the kindergartens, to measure the le indoor air quality and also to analyze respiratory health symptoms. Three kindergartens were selected based on types of building J Fundam Appl Sci. 2017, 9(4S), 801-811 802The exposure history and respiratory health symptoms data among respondent in the study area were being collected by using questionnaire. Sampling for IAQ also being conducted and parameters involved for this purposed included carbon monoxide, carbon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…According to ICOP 2010, CO₂ exposure should not exceed 1000 ppm for an 8-hour period. Ten studies investigated indoor CO₂ with mean and median concentrations ranging between 537.04 ppm to 1680.35 ppm [31], [32], [34], [36], [39], [40], [43], [45]- [47]. Kindergartens in urban areas recorded high levels of CO₂ compared to kindergartens situated in suburban and rural areas [34], [36], [43].…”
Section: Carbon Dioxidementioning
confidence: 99%
See 3 more Smart Citations
“…According to ICOP 2010, CO₂ exposure should not exceed 1000 ppm for an 8-hour period. Ten studies investigated indoor CO₂ with mean and median concentrations ranging between 537.04 ppm to 1680.35 ppm [31], [32], [34], [36], [39], [40], [43], [45]- [47]. Kindergartens in urban areas recorded high levels of CO₂ compared to kindergartens situated in suburban and rural areas [34], [36], [43].…”
Section: Carbon Dioxidementioning
confidence: 99%
“…The findings of this study coincided with Rahman et al [45] as all air-conditioned classrooms in three kindergartens also recorded CO₂ levels between 1068-1090 ppm with a capacity of 16, 19 and 24 children in each kindergarten. Most kindergartens with natural ventilation systems recorded CO₂ level below 1000 ppm [34], [36], [37], [43], [47]. However, Nahar and Salleh [46] found that a high density of 19-22 students in each classroom utilizing natural ventilation also contributed to high CO₂ levels.…”
Section: Carbon Dioxidementioning
confidence: 99%
See 2 more Smart Citations
“…The Air Quality [17][18][19][20][21][22][23][24][25] Guidelines set for the first time a guideline value for particulate matter and the aim of the guidelines is to achieve the lowest concentrations of pollutant in atmosphere as possible [11].…”
Section: Review Of Literaturesmentioning
confidence: 99%